Cancer Stem Cell Markers in Head and Neck Squamous Cell Carcinoma. (3rd March 2013) - Major, Aidan G.; Pitty, Luke P.; Farah, Camile S.
Abstract : Head and neck squamous cell carcinoma (HNSCC) is one of the world's top ten most common cancers. Current survival rates are poor with only 50% of patients expected to survive five years after diagnosis. The poor survival rate of HNSCC is partly attributable to the tendency for diagnosis at the late stage of the disease. One of the reasons for treatment failure is thought to be related to the presence of a subpopulation of cells within the tumour called cancer stem cells (CSCs). CSCs display stem cell-like characteristics that impart resistance to conventional treatment modalities and promote tumour initiation, progression, and metastasis. Specific markers for this population have been investigated in the hope of developing a deeper understanding of their role in the pathogenesis of HNSCC and elucidating novel therapeutic strategies.